Instructional materials in English for scientific purposes with focus on biology for second year high school students - Buenconsejo, Leonor M. (1977)
These instructional materials, which consist of 12 lessons integrating English with biology for use in the second year high school, have been designed to meet the need for materials that will facilitate instruction in the kind of English required by Filipino students in the discipline of science and mathematics. This set focuses on information-getting in scientific prose via reading and listening and information-transfer through writing and speaking. The scientific process chosen as springboard dictates more or less specific lexical and syntactic structures. These structures are mainly the teaching items for grammar and composition. It is hoped that the accompanying guide to the use of these materials will prove useful and clarify certain other points while allowing for the teacher-user's improvement of them to suit his own needs.